Strategies of Distinction
1 online resource (374 pages)
Keywords: Between the fourth and the eight century, a number of 'experimental' polities had to create new forms of legitimacy and organisation to overcome a Roman world based on Empire, city and tribe. In the course of time, a new world developed that relied on Christendom, kingdom and people to pull an increased variety of local communities together. Of these three factors, the ethnic one certainly is the most elusive. This volume discusses the process of construction of ethnic identities. What did names, law, language, costume, burial rites, rhetoric, culture, royal representation or ideology mean, and to whom? This is the question that is common to the papers assembled here. Even though they span several centuries, and a geographic area from the Iberian peninsula to the Black Sea steppes, they all deal with the ways how ethnic distinction became a political factor in the post-Roman world.